Protective effect of Esculin in adjuvant-induced arthritic (AIA) rats via attenuating pro-inflammatory cytokines and oxidative stress - Zheng, L; Yang, L; Wang, Z; Chen, C; Su, Y (Cellular and Molecular Biology, 2015)
The present study was intended to exemplify the protective effect of Esculin (ES; 6,7-dihydroxycoumarin-6-o-glucoside) on the adjuvant induced arthritis in adult female Sprague Dawley rats. It has been found that, treatment of ES has significantly improved the body weight of rats accompanied with a reduction of paw volume in comparison to arthritic control. In addition, ES exhibit inhibitory effect on various pro-inflammatory cytokines, for instance, IL-1Î² and TNF-Î±. The level of oxidative stress markers, i.e., nitric oxide and peroxide was also found suppressed after treatment. The treatment of ES prevents the tissue injury mediated via oxidative stress via up-regulating the level of endogenous GSH in a dose dependent manner. Thus, it has been corroborated that, ES exerts potent anti-arthritic activity via attenuating pro-inflammatory cytokines and oxidative stress.